The Drilling Method Application Using Abacus to Arithmetic Operations Skills in Student with Hearing Impairment at Special School - Endang Rusyani; Een Ratnengsih; Andri Syah Putra; Rina Maryanti; Dwi Fitria Al Husaeni; Risti Ragadhita (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study was to determine the effect of the drilling method application using abacus in improving arithmetic subtraction operations skills in deaf children. This study used an experimental method with Single Subject Research (SSR), A-B-A design. The drilling method was used in the learning process. In addition, the abacus media was also used in the subtraction arithmetic operation material in learning mathematics. The results showed that there was an effect of applying the drilling method using abacus in improving the arithmetic subtraction operation skills in deaf children with the initials SS. This could be seen from the increase in the mean level of student’s abilities starting from baseline-1 (A1) by 30%, intervention (B) by 65%, and baseline-2 (A2) by 86.66%. The methods and media were suitable to make the lesson easier to understand for students. The drilling method with the abacus media could be used as an alternative for teachers in improving the skills of arithmetic subtraction operations in deaf children. The results of this study are expected to contribute to developing special education related to the application of the drilling method using abacus media to improve arithmetic operations skills in learning next math.